"The history of Mary Prince": (The first narrative by a slave woman to be published in Britain) - Shaw, Damian (My University, 1999)
The History of Mary Prince (1831) is, as far as we know, the first and only account by a slave woman of her experiences to be published in Britain.(1) Its publication caused an immediate uproar which provoked three further editions within a year, (2) a petition on her behalf to the British Parliament, two vicious attacks against it in contemporary journals, (3) and two court cases for libel. At Prince's request, the biography was dictated for publication to her friend, the poet Susanna Strickland, in the Pringle's drawing room in London. (4) The account was then edited by Thomas Pringle after examining Mary as to its veracity. (5) Pringle stated that: 'The narrative was taken down from Mary's own lips by a lady who happened to be at the time residing in my family as a visitor. It was written out fully, with all the narrator's repetitions and prolixities, and afterwards pruned into its present shape; retaining, as far as was practicable, Mary's exact expressions and peculiar phraseology. No feet of importance has been omitted, and not a single circumstance or sentiment has been added. It is essentially her own, without any material alteration farther than was requisite to exclude redundancies and gross grammatical errors, so as to render it clearly intelligible.'(6) Paul Edwards and David Dabydeen say, correctly, that 'the truth of Pringle's editorial comment is borne out by the language of the narrative.' They support their argument with several examples drawn from the narrative, including, as they say, Prince's ‘down-to-earth’ expression, use of creolized English, 'live' situation reportage and ‘admissions of the difficulty of expressing herself’ (7) This narrative, then, stands in stark contrast to most edited slave narratives of the period where 'all Africanisms, all the special images and metaphors from the vernacular, were suppressed.' (8) Proceeds of the publication were given to a fund for Mary's future benefit. (9)
African Studies Seminar series. Paper presented 27 September 1999
Keywords: Prince, Mary; Fugitive slaves. West Indies. Biography; Slavery. West Indies